Next-Generation Sequencing Enhances the Diagnosis Efficiency in Thyroid Nodules - Tan, Li-Cheng; Liu, Wan-Lin; Zhu, Xiao-Li; Yu, Peng-Cheng; Shi, Xiao; Han, Pei-Zhen; Zhang, Ling; Lin, Liang-Yu; Semenov, Arseny; Wang, Yu; Ji, Qing-Hai; Ji, Dong-Mei; et al. (Frontiers in Oncology, 2021)
Background: Though fine-needle aspiration (FNA) improved the diagnostic methods of thyroid nodules, there are still a part of nodules cannot be determined according to cytology. In the Be-thesda system for reporting thyroid cytopathology, there are two uncertain cytology results. Thanks to the development of next-generation sequencing technology, it is possible to gain the genetic background of pathological tissue efficiently. Therefore, combination of the cytology and genetic background may enhance the accuracy of diagnosis in thyroid nodules. Methods: DNA from 73 FNA samples of thyroid nodules belong to different cytology types was extracted and exome sequencing was performed by the ThyroLead panel. Test for BRAF mutation was also performed by ARMS-qPCR. Information including age, sex, preoperative cytology, BRAF mutation status tested by ARMS-qPCR, surgical pathology was collected in electronic medical record system. Results: A total of 71 single nucleotide variants, 3 fusion gene, and 2 microsatellite instability-high status were detected in 73 FNA samples. BRAF V600E mutation is the most common mutation in these malignant thyroid nodules. After combining the cytology and genetic background detected by next-generation sequencing, the diagnosis sensitivity was increased from 0.582 (95% CI: 0.441-0.711) to 0 0.855 (95% CI: 0.728-0.930) (P < 0.001) in our group, while the specificity, 1.000 (95% CI: 0.732-1.000) compared to 0.857 (95% CI: 0.562-0.975) (P = 0.25), didn’t get affected. Conclusions: Next-generation sequencing in thyroid nodules can enhance the preoperative diag-nosis sensitivity by fine-needle aspiration alone. It can also provide genetic background for direc-tion of medication. It is possible for clinicians to combine cytology with genetic alterations for a more precise diagnosis strategy of thyroid nodules.